El perfil sociodemográfico del lector de libros en España (1975-2010) - Palacios Gómez, José Luis; Burgos Bordonau, Esther (Revista General de Información y Documentación, 2010)
The aim of this article is to define the socio-demographic features of the Spanish books readers’ and their changes from 1975 to 2010. Sufficiently resolved the problem of sources heterogeneity for a wide part of the period, the time series of books readers’ rates is defined and statistically modeled. The books readers’ rate longitudinal analysis by means of their socio-demographic features segmentation shows that typical profile of books reader in Spain has suffered a small structural variation, being the most notorious change that one related with the sex: whereas the profile of books reader in the beginning of the observed period was defined by a young man, student and graduated, nowadays it’s a woman with the same features.